Akibat Hukum Wanprestasi Dalam Pelaksanaan Perjanjian Berdasarkan Pasal 29 Undang-Undang Nomor 42 Tahun 1999 Tentang Jaminan Fidusia - Anak Agung Dewi Utari (Prodi Hukum S1 - Fakultas Hukum - Universitas Pamulang, 2025)
The legal consequences of defaulting debtors in standard agreements are the same as agreements in general, where the debtor is required to pay compensation for the losses suffered by the creditor, the creditor can demand termination/cancellation of the engagement through a judge, the risk shifts to the debtor since the default, the debtor is obliged to fulfill the agreement if can still be done or cancellation accompanied by a claim for compensation, the debtor. Efforts to resolve default in the event of credit, namely providing guidance to debtors who have non-performing loans are carried out by the analyst concerned. Reconditioning or reconditioning, namely providing conditions for returning loans that have been given by changing various existing requirements such as interest capitalization which is used as the principal debt, interest rate reductions aimed at easing the burden on the debtor, and interest exemption with the consideration that the debtor will be able to repay the loan. until paid off.